ANALISIS PENDAPATAN DAN EFISIENSI EKONOMI PENGRAJIN TEMPE DARI HOME INDUSTRI (Studi Kasus Desa Sentong Krajan Kecamatan Krejengan Kabupaten Probolinggo) - Ade Istihar Desman; Sudarti; Zainal Arifin (Jurnal Ilmu Ekonomi JIE, 2019)
The study aims to 1) determine the income level of tempe producers in the use of production factors in Probolinggo District 2) to assess the level of economic efficiency of tempe producers in the use of production factors in Probolinggo Regency. The type of research that does this is survey research. In this study the population of the home industry owner was 11 respondents. Data collected later tabulated then analyzed descriptively and inferentially so that the objectives and research conducted were achieved. The results of the analysis can be seen that the income level of tempe producers in the use of production factors in Probolinggo Regency shows that the highest level of acceptance of tempe producers is Rp. 796,000, - while the lowest is Rp. 660,000, -. Overall the amount of income obtained by craftsmen is Rp. 7,782,000, - with an average value of Rp. 707,454.5. The results of the analysis of the level of economic efficiency of tempe producers in the use of production factors in Probolinggo Regency can be seen that the R / C value ≥ 1, means that the tempe home industry is run efficiently or profitably, this is indicated by the highest efficiency value of 1.520548 and the lowest 1.169728.